2023
DOI: 10.3390/foods12112259
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Processed Vegetables in Brazil: An Overview of Marketing, Processing, and Microbiological Aspects

Abstract: The global demand for minimally processed vegetables (MPVs) has grown, driven by changes in the population’s lifestyle. MPVs are fresh vegetables that undergo several processing steps, resulting in ready-to-eat products, providing convenience for consumers and food companies. Among the processing steps, washing–disinfection plays an important role in reducing the microbial load and eliminating pathogens that may be present. However, poor hygiene practices can jeopardize the microbiological quality and safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Healthy transplants could initiate the process of successful crop production. When performed in accordance with good, mechanized practices, these main vegetables would grow evenly and mature at similar stages, increasing the likelihood of rejection by consumers and markets [3]. The performance tests showed that the average success ratio in transplanting seedlings for the three local vegetable crops was more than 90% when the transplanting rate was 15 seedlings per minute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy transplants could initiate the process of successful crop production. When performed in accordance with good, mechanized practices, these main vegetables would grow evenly and mature at similar stages, increasing the likelihood of rejection by consumers and markets [3]. The performance tests showed that the average success ratio in transplanting seedlings for the three local vegetable crops was more than 90% when the transplanting rate was 15 seedlings per minute.…”
Section: Discussionmentioning
confidence: 99%
“…For the effects of different morphological and physical characteristics of plug seedlings, the adaptability to fully automatic machinery might be investigated for high-quality transplants [31]. The development of seedling low-loss transplantation with the coordinated promotion of minimally processed vegetables would effectively improve the utilization level of fresh vegetables [3,12]. Through continuous technological innovation, it is conducive to the healthy development of the vegetable industry while protecting the interests of upstream vegetable farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ready-to-use products do not require additional preparation before being consumed and can be found on the market in a wide variety, like fresh-cut fruits, salads and vegetables, cooked meat and poultry, smoked/salted seafood, smoked/salted meat, and dairy [1]. Ready-to-use vegetable salads are minimally processed products [3], by sorting, cutting, washing/disinfection, rinsing, centrifugation, packaging in air or a modified atmosphere, refrigeration and transport, which are finally consumed in a short period of time [4,5]. According to Ülger et al [6], about 10,000 plant species are considered vegetables, and they are classified as follows: leaf vegetables (chard, chicory, curly lettuce, lettuce, purslane and spinach); stalk vegetables (celery and asparagus), flowering vegetables (broccoli, cauliflower and artichoke); root, bulb and tuber vegetables (beet, carrot, fennel, onion, potato, radish and turnip); and legumes (peas and soya beans).…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, 225.4 thousand ha of vegetables were cultivated in the country, with a total production of 3501.4 thousand tones (cabbage, with 977.4 thousand tones, and tomatoes, with 712.2 thousand tones, being the most cultivated). Rich in vitamins, minerals, dietary fiber content and phytochemicals, vegetables play an important role in human health [5], and it is recommended to consume 400 g of vegetables and fruits per day (of which 240 g should be vegetables) [8,9] for the prevention of stroke, high blood pressure, cardiovascular diseases and other micronutrient deficiencies [10]. In 2021, an average of 364.58 g of fruit and vegetables per day per capita were consumed in the EU, being below the minimum recommended [11].…”
Section: Introductionmentioning
confidence: 99%